Transcranial Direct Current Stimulation over the Right Inferior Parietal Cortex Reduces Transposition Errors in a Syllabic Reordering Task - Vanessa Costa (MDPI AG, 2021)
Evidence derived from functional imaging and brain-lesion studies has shown a strong left lateralization for language, and a complementary right hemisphere dominance for visuospatial abilities. Nevertheless, the symmetrical functional division of the two hemispheres gives no reason for the complexity of the cognitive operations involved in carrying out a linguistic task. In fact, a growing number of neuroimaging and neurostimulation studies suggest a possible right hemisphere involvement in language processing. The objective of this work was to verify the contribution of the left and right parietal areas in a phonological task. We applied anodal transcranial direct current stimulation (tDCS) to the right or left inferior parietal lobe, during a syllabic reordering task. After having learnt a combination of images of real objects and trisyllabic pseudowords with a simple consonant–vowel (CV) syllabic structure (e.g., tu-ru-cu), participants were shown the same images paired to two different pseudowords: one correct but with transposed syllables, and one alternative, never before seen. The participant’s task was to orally produce the chosen pseudoword, after having rearranged the order of its syllables. Two types of error were considered: transposition (correct pseudoword but incorrectly reordered) and identity (incorrect pseudoword). The results showed that right anodal stimulation significantly reduced the number of transposition errors, whereas left anodal stimulation significantly reduced the number of identity errors. These results suggested that both left and right inferior parietal areas were differentially involved in a syllabic reordering task, and, crucially, they demonstrated that visuospatial processes served by the right inferior parietal area could be competent for establishing the correct syllabic order within a word.